C-peptide, liver enzymes and CRP-protein related with vitamin D deficiency in obese and diabetic (type 2) women - Farah Kadhim Alwan; Ahmed Aboud khalifa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study aims to investigate the relationship of vitamin D deficiency and some other biochemical parameters (C-peptide, Alanine transaminase ALT, Aspartate transaminase AST, Alkaline phosphatase ALP and C-reactive protein CRP) levels in obese and diabetic women. The whole sample included 60 women aged 30 – 40 years, divided to three groups (20 women / group) as control, obesity and diabetes groups (the participants in obesity and diabetes groups were diagnosed with vitamin D deficiency). Results revealed: C-peptide increased significantly (p  ≤  0.01 ) in obesity group and not significantly in diabetes group in comparison with the control , ALT increased significantly (p  ≤  0.01 ) in different groups in comparison with the control , AST increased not significantly in different groups in comparison with control, ALP  increased  significantly (p  ≤  0.01 ) in diabetes group and significantly (p  ≤  0.05 ) in obesity group in comparison with the control, CRP increased significantly (p  ≤  0.01 ) in different groups in comparison with the control. The physiological impacts of these results be discussed according to the impact of vitamin D deficiency that associated with different metabolic and inflammatory disturbances, leading to diverse detrimental influence on the biochemical profiles of the studied groups.DOI: https://doi.org/10.54633/2333-024-056-009